Addressing issues on quality in low cost house construction in Selangor / Muhammad Firdaus Abd Razak and Mohd Fadzil Mat Yasin - Abd Razak, Muhammad Firdaus; Mat Yasin, Mohd Fadzil (2018)
A growing population in Malaysia demand for housing has also increased and the government has provided low cost housing to those with low household income. This is to give them the opportunity to have their own homes. For that reason many issues raised about low-cost houses. This paper discussed the quality issue of low cost house construction. Therefore the aim of this study is to study the quality issue of low cost housing in Malaysia. The objectives of this research are to explore the current quality issues for the development of low-cost housing and to identify the factors that influence the quality of low-cost houses in Malaysia. A literature review has been carried out and research was conducted among contractor G7 in Selangor State. The data collection of this research is by questionnaire and was analyzed by using SPSS with Version 24 which the latest one and Average Index Method. From the data collected and analyzed, the finding indicated that there are six factors that affect the quality of low cost housing construction and should be noted in order to get good quality of the house.